2018
DOI: 10.1101/436030
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of ZnT8 function protects against diabetes by enhanced insulin secretion

Abstract: 69A rare loss-of-function variant p.Arg138* in SLC30A8 encoding the zinc transporter 8 (ZnT8) 70 enriched in Western Finland protects against type 2 diabetes (T2D). We recruited relatives of the 71 identified carriers and showed that protection was associated with better insulin secretion due to 72 enhanced glucose responsiveness and proinsulin conversion, especially compared with individuals 73 matched for the genotype of a common T2D risk variant in SLC30A8, p.Arg325. In genome-edited 74 human IPS-derived β-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…Strikingly, the vast majority affect insulin secretion rather than insulin action. Several laboratories, including our own, have provided possible mechanisms of action for some of the implicated genes, including TCF7L2, encoding the Wnt-regulated transcription factor [ 10 ], SLC30A8 encoding zinc transporter 8 (ZnT8, the secretory granule zinc transporter) [ 11 ], PAM , encoding peptidylglycine α-amidating monooxygenase [ 12 ] and STARD10 , encoding an intracellular lipid transporter [ 13 ]. The reader is referred to the recent review by Krentz and Gloyn [ 14 ] for a more comprehensive survey.…”
Section: Specialisations Of Beta Cell Metabolismmentioning
confidence: 99%
“…Strikingly, the vast majority affect insulin secretion rather than insulin action. Several laboratories, including our own, have provided possible mechanisms of action for some of the implicated genes, including TCF7L2, encoding the Wnt-regulated transcription factor [ 10 ], SLC30A8 encoding zinc transporter 8 (ZnT8, the secretory granule zinc transporter) [ 11 ], PAM , encoding peptidylglycine α-amidating monooxygenase [ 12 ] and STARD10 , encoding an intracellular lipid transporter [ 13 ]. The reader is referred to the recent review by Krentz and Gloyn [ 14 ] for a more comprehensive survey.…”
Section: Specialisations Of Beta Cell Metabolismmentioning
confidence: 99%
“…Ultimately, prioritized genes need to be validated in human models, as demonstrated for a mutation in SLC30A8 (encoding ZnT8). In a recall-by-genotype study with detailed metabolic phenotyping, it was shown that carriers were protected from T2D through enhanced glucose responsiveness and proinsulin conversion, making SLC30A8 /ZnT8 an appealing target for antidiabetic therapies 8 . The generation of new data and development of advanced technologies and analytical approaches will continue to facilitate the translation of a growing number of GWAS loci into meaningful biology and clinical targets in many years ahead.…”
Section: Boxmentioning
confidence: 99%
“…Genetic variants in the Zn 2+ transporter SLC30A8 ( ZNT8 ), present in the membrane of insulin granules, have been associated with T2D susceptibility ( 70 , 71 ). A rare loss of function mutation in ZNT8 protects against T2D, making this Zn 2+ transporter a potentially interesting therapeutic target ( 72 ).…”
Section: Beta Cell Insulin Secretion Defectsmentioning
confidence: 99%